Inter-community Relations Factor on the Empowerment of the Aisle Community in Makassar City: A Structural Equation Model - Palutturi, Sukri; Saleh, Lalu Muhammad; Rachmat, Muhammad; Shabir, Achmad Mawardi; Rosmanely, St.; Aidillah, Muhammad Rafli; Malek, Jalaluddin Abdul; Nam, Eun Woo (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: There are several important factors in building community empowerment, one of them is the inter-community relationship. However, further research is rarely done on this dimension. The dimension of the relationship includes community structure, community strength, community motivation, community communication, community integrity, community participation, and community development. Objective: This study aimed to find the best model of the effect of the inter-community relationship on the condition of healthy aisle in Makassar City. Method: This research was conducted in 2 sub-districts in Makassar City, those are Rappocini District and Ujung Tanah District. The research samples involved were 560 households in Lorong. Data analysis was performed using multivariate analysis through the structural equation model (SEM) test. Results: The results of this study found that clear vision (CR = 3.219 and p = 0.01), capacity development (CR = 3.166 and p = 0.02), norms existence (CR = 3.143 and p = 0.02) on inter-community relationship significantly affected the aisle community empowerment. Conclusion: Inter-community relationship is the best model in developing a healthy aisle in Makassar City through solidarity, shared motivation, shared trust, clear vision, resources shares, capacity building, norms in society, government support, and community development. This study recommends that in order to maximize a clear vision for the aisle community working group, the government should carry out legality regarding the aisle community structure.